Development of the “TeachABK” Big Book to Improve the Speaking Skills of Children with Speech Delay - Reni Fadhilah; Sovi Amalia; Aunia Shifni El Wardah; Ratna Nulinnaja (Jurnal Paedagogy, 2026)
This study aims to develop a learning instrument, the "TeachABK" Big Book, designed to stimulate the verbal competence of children with speech delays at MI Al-Hidayah, Malang Regency. This study adopts a Research and Development (R&D) approach using the ADDIE instructional design model. The resulting product is an A4-sized learning medium that integrates adaptive visual design, simplified text, and audio-based QR code features to support students’ articulation. Data were collected through observations, interviews, documentation, and questionnaires. The effectiveness of the media was evaluated using both qualitative and quantitative data analyses, including the N-Gain test. Based on expert validation of both material and media aspects, the "TeachABK" Big Book achieved a "very good" rating, with scores exceeding the 85% threshold. Field implementation results indicate significant improvements in students’ speaking abilities, particularly in vocabulary development, pronunciation clarity, and the ability to produce simple sentence structures. Both theoretically and practically, these findings highlight that personalized and interactive media innovations serve as essential tools in strengthening the implementation of inclusive education at the elementary school level.